Implementasi Kebijakan Sistem Rumputisasi Makam Covid-19 oleh Dinas Cipta Karya, Bina Konstruksi, Dan Tata Ruang (Studi Kasus pada Unit Pelaksana Teknis (UPT) Wilayah 3 Taman Pemakaman Umum (TPU) Cikadut Kota Bandung) - Alifansyah, Mochamad Zeni; Pangestu, Fikri Aditia; Majid, Miftah Khoirul; Hardian, Hadi; Lisna, Lisna (LITERATUS, 2025)
Cemetery land is not just a location for Public Cemeteries (TPU), but also an area for various types0of plants, especially green plants such as fruiting trees, grass, and other plants. The population growth rate is the main cause of the increasing number of deaths in all regions, especially in Bandung City. In accordance with Bandung City Regional Regulation Number 5 of 2025, it states that the government recommends the implementation of TPU grassing activities in stages for graves that are grassed by the government at no cost to the heirs. This research aims to find out the implementation of the cemetery grassing system policy as well as the obstacles and efforts made by the Cikadut TPU Office, Bandung City. This type of research is qualitative with a descriptive case study approach where this research describes or describes each real event in written form. Data collection techniques with interviews, observation, and documentation. In this study, the theory used by researchers is the theory of implementation according to Charles O. Jones which includes organization, interpretation, and application. The results showed that the policy implementation of the cemetery grass system at the Cikadut TPU Office in Bandung City was already running well, but there were still obstacles that occurred in the field. In the organizational aspect, it has gone well, such as increasing awareness0and knowledge of employees and the community about the challenges of this grassroots system and knowing the organization in these indicators. Second, this interpretation has been running according to its development. Third, this application has been running well based on the response of managers and the community as well as based on the monitoring and evaluation carried out.